Playing by the rules? New institutionalism, path dependency and informal settlements in Sub-Saharan Africa. (November 2017) - Morrison, Nicky
The scale of contemporary urbanization in Sub-Saharan Africa has culminated in the proliferation of informal settlements, with governments claiming a legitimate right to remove them. Drawing on new institutionalism as a conceptual framework and presenting the case of Old Fadama, an informal settlement within central Accra in Ghana, this paper sheds light on the way in which both formal and informal rules shape these legally unauthorized spaces. Using the analogy of a game, the author devises a novel typology to highlight the way in which different players maximize their personal advantage from maintaining the status quo. The paper concludes that as long as different interests are served by the existing socio-political arrangements then path dependency will endure, with government officials as the dominant playmaker in the locality ultimately controlling the rules and pace of the game.